Unternehmerische Verantwortung in Lieferketten - Jung, Peter; Schroeter, Ulrich G. (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
On 6 May 2022, the Ernst von Caemmerer Foundation and the European Law Institute, organised at the University of Basel a conference on "Corporate Responsibility in Supply Chains". In presentations by Eva-Maria Kieninger, Giesela Rühl, Patrick C. Leyens, Ulrich G. Schroeter and Pascal Hachem the various approaches to the protection of human rights and the environment in supply chains were addressed, taking into account foreign law experience and the EU Commission's proposal for a directive of 23 February 2022. Aspects of international civil procedure law and private international law were also taken into account, as well as the practical handling of these issues in the practice of companies and their advisors.With Contribution byPaula Blank, MLaw, LL.M. | RA Dr. Pascal Hachem | Prof. Dr. Peter Jung, Maître en Droit (Toulouse) | Prof. Dr. Eva-Maria Kieninger | Prof. Dr. Patrick C. Leyens, LL.M. (London) | Prof. Dr. Giesela Rühl, LL.M. (Berkeley) | Prof. Dr. Ulrich G. Schroeter